In Vitro Anticancer Activity of a Nonpolar Fraction from Gynostemma pentaphyllum (Thunb.) Makino. (29th February 2016) - Li, Yantao; Huang, Jiajun; Lin, Wanjun; Yuan, Zhongwen; Feng, Senling; Xie, Ying; Ma, Wenzhe
Abstract : Gynostemma pentaphyllum (Thunb.) Makino (GpM) has been widely used in traditional Chinese medicine (TCM) for the treatment of various diseases including cancer. Most previous studies have focused primarily on polar fractions of GpM for anticancer activities. In this study, a nonpolar fraction EA1.3A from GpM showed potent growth inhibitory activities against four cancer cell lines with IC50 ranging from 31.62  μ g/mL to 38.02  μ g/mL. Furthermore, EA1.3A also inhibited the growth of breast cancer cell MDA-MB-453 time-dependently, as well as its colony formation ability. EA1.3A induced apoptosis on MDA-MB-453 cells both dose-dependently and time-dependently as analyzed by flow cytometry and verified by western blotting analysis of apoptosis marker cleaved nuclear poly(ADP-ribose) polymerase (cPARP). Additionally, EA1.3A induced cell cycle arrest in G0/G1 phase. Chemical components analysis of EA1.3A by GC-MS revealed that this nonpolar fraction from GpM contains 10 compounds including four alkaloids, three organic esters, two terpenes, and one catechol substance, and all these compounds have not been reported in GpM. In summary, the nonpolar fraction EA1.3A from GpM inhibited cancer cell growth through induction of apoptosis and regulation of cell cycle progression. Our study shed light on new chemical bases for the anticancer activities of GpM and feasibilities to develop new anticancer agents from this widely used medicinal plant.